Cognitive composite score association with Alzheimer’s disease plaque and tangle pathology - Malek-Ahmadi, Michael (Alzheimers Res Ther, 2018)
BACKGROUND: Cognitive composite scores are used as the primary outcome measures for Alzheimer’s disease (AD) prevention trials; however, the extent to which these composite measures correlate with AD pathology has not been fully investigated. Since many on-going AD prevention studies are testing therapies that target either amyloid or tau, we sought to establish an association between a cognitive composite score and the underlying pathology of AD. METHODS: Data from 192 older deceased and autopsied persons from the Rush Religious Order Study were used in this study. All participants were classified at their initial evaluations with a clinical diagnosis of no cognitive impairment (NCI). Of these individuals, 105 remained NCI at the time of their death while the remaining 87 progressed to mild cognitive impairment (MCI) or AD. A cognitive composite score composed of eight cognitive tests was used as the outcome measure. Individuals were classified into groups based on Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) neuropathological diagnosis and Braak stage. RESULTS: The rate of annualized composite score decline was significantly greater for the high CERAD (p < 0.001, d = 0.56) and Braak (p < 0.001, d = 0.55) groups compared with the low CERAD and Braak groups, respectively. Mixed-model repeated measure (MMRM) analyses revealed a significantly greater difference in composite score change from baseline for the high CERAD group relative to the low CERAD group after 5 years (Δ = −2.74, 95% confidence interval (CI) −5.01 to −0.47; p = 0.02). A similar analysis between low and high Braak stage groups found no significant difference in change from baseline (Δ = −0.69, 95% CI −3.03 to 1.66; p = 0.56). CONCLUSIONS: These data provide evidence that decreased cognitive composite scores were significantly associated with increased AD pathology and provide support for the use of cognitive composite scores in AD prevention trials.